Congenital Cystic Adenomatoid Malformation (CCAM) Type II: A Rare Case of Sudden Infant Death - Monica Salerno; Francesco Sessa; Giuseppe Cocimano; Salvatore Roccuzzo; Massimiliano Esposito; Cristoforo Pomara (MDPI AG, 2022)
Congenital cystic adenomatoid malformation (CCAM) is a developmental lesion of the lungs and terminal respiratory structures, which is characterized by pseudocysts, lesions, and cystically dilated airways. CCAM is also known as congenital pulmonary airway malformation (CPAM). Various classification systems for CCAM have been described, and based on a recent classification, CCAMs are classified morphologically into five different types (Type 0, I, II, III, and IV) based on lesion sizes. The most common manifestation of CCAM in neonates and children is respiratory distress (RD). Spontaneous pneumothorax is a rare manifestation of CCAM. In this case report, we discuss a CCAM type-II case of a 38-day-old female infant with a radiological post-mortem diagnosis of a large left-side spontaneous pneumothorax. The gross examination of the lungs revealed multiple emphysematous air bubbles up to 0.5 cm in diameter, and the histological examination revealed focal pleural fibrosis, accompanied by thickened septa and atelectasis. In this scenario, the routine use of prenatal ultrasonography would be important to obtain a timely prenatal diagnosis. At the same time, improvements in surgical techniques, as well as greatly improved imaging techniques, have improved the outcome of these patients. Finally, it is important to remark on the importance of autopsy in the case of sudden infant death with a suspected CCAM.